PLANNING THROUGH COMMUNITY: AN EVALUATION OF THAILAND’S BAAN MANKONG PROGRAM - Hayden Shelby (PEOPLE: International Journal of Social Sciences, 2026)
In this paper, I put forward the concept of “planning through community” to describe the efforts of many urban actors throughout the world to use ’community’ to do planning, rooted in the belief that if communities have greater participation in citymaking, then cities will be more just. However, grassroots activists and policymakers alike continually confront the fact that communities aren’t already ’out there’ to do the kind of participation they envision. The communities themselves must first be planned, through various methods of organizing, building, or development. Through these processes, communities become both the object and subject of planning. The analysis of the paper is based on ten years of studying the Baan Mankong (“Secure Housing”) program of Thailand, which uses collective land tenure and community-managed finance to provide residents of self-built settlements land rights and resources for physical upgrading. As an international best practice that has reached over 120,000 households, Baan Mankong is an exemplary case of planning through community. Like many such cases, its advocates aim to achieve a nebulous vision of "empowerment." But as I will show, the program can also produce injustice, relying heavily on the unpaid labor and limited resources of participants, calling upon them to act as a substitute for state provision. I argue that in planning through community, empowerment and responsibility are two sides of the same coin. The complex story of Baan Mankong offers a provocation to scholars and practitioners to think more deeply about how we might land on the right side of the coin more often.